Height-reducing variants and selection for short stature in Sardinia - Zoledziewska, Magdalena; Sidore, Carlo; Chiang, Charleston W K; Sanna, Serena; Mulas, Antonella; Steri, Maristella; Busonero, Fabio; Marcus, Joseph H; Marongiu, Michele; Maschio, Andrea; Del Vecchyo, Diego Ortega; Floris, Matteo; et al. (Nature genetics, 2015)
Francesco Cucca, David Schlessinger, John Novembre, Gonçalo Abecasis and colleagues present sequencing-based whole-genome association analyses for stature in Sardinia and identify two variants that lead to reduced height. Their findings suggest that shorter stature was selected for in Sardinia. We report sequencing-based whole-genome association analyses to evaluate the impact of rare and founder variants on stature in 6,307 individuals on the island of Sardinia. We identify two variants with large effects. One variant, which introduces a stop codon in the GHR gene, is relatively frequent in Sardinia (0.87% versus <0.01% elsewhere) and in the homozygous state causes Laron syndrome involving short stature. We find that this variant reduces height in heterozygotes by an average of 4.2 cm (−0.64 s.d.). The other variant, in the imprinted KCNQ1 gene (minor allele frequency (MAF) = 7.7% in Sardinia versus <1% elsewhere) reduces height by an average of 1.83 cm (−0.31 s.d.) when maternally inherited. Additionally, polygenic scores indicate that known height-decreasing alleles are at systematically higher frequencies in Sardinians than would be expected by genetic drift. The findings are consistent with selection for shorter stature in Sardinia and a suggestive human example of the proposed 'island effect' reducing the size of large mammals.